The Effect of Ethanol Blending on Combustion and Soot Formation in an Optical DISI Engine Using High-Speed Imaging - Erdenkäufer, Stefan; Will, Stefan; Wensing, Michael; Zigan, Lars; Storch, Michael (The 12th International Conference on Combustion and Energy Utilisation, 2015)
Biofuel components exhibit significantly different fuel properties as compared to gasoline leading to a very complex chain of effects in engine combustion. Therefore, the effects of varying composition on mixture formation, combustion and soot formation can hardly be predicted. In this study, the influence of blending 20vol% ethanol to isooctane is investigated by simultaneous 011*-chemiluminescence and soot radiation high-speed imaging. For both fuels engine load was varied for a typical catalyst heating operating point, which is characterized by increased soot formation probability. The study reveals an unexpected behavior for Eat Both the 011*-chemiluminescence and soot luminosity intensity are higher as compared to isooctane. Furthermore, for E20 the occurrence probability of droplet combustion is increased. High engine load increases the combustion intensities and probability of soot formation for both investigated awls. (C) 2015 The Authors. Published by Elsevier Ltd. This is an Ten access article under the CC BY-NC-ND license (http://creativecommons.orglicenses/by-nc-nd/4.0/).
Keywords: DISI engine; Isooctane/ethanol blends; OH*-chemiluminescence; soot radiation